2013
DOI: 10.1155/2013/315023
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of No-Primer Adhesives and Anchor Pylons Bracket Bases on Shear Bond Strength of Orthodontic Brackets

Abstract: Objective. The aim of this study was to compare the shear bond strength (SBS) and adhesive remnant index (ARI) scores of no-primer adhesives tested with two different bracket bases. Materials and Methods. 120 bovine permanent mandibular incisors were divided into 6 groups of 20 specimens. Two brackets (ODP) with different bracket bases (anchor pylons and 80-gauge mesh) were bonded to the teeth using a conventional adhesive (Transbond XT) and two different no-primer adhesive (Ortho Cem; Heliosit) systems. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 25 publications
4
43
3
1
Order By: Relevance
“…After bias risk analysis (Table 1), one study 11 was excluded due to its high risk of bias. Nine studies 2,3,8,[12][13][14][15][16][17] were included; descriptive data, random-effect means, confidence interval, and weight of each study are shown in Table 2. The lowest mean for bond strength in a group was 6.42 MPa; the highest value was 34.8 MPa, with 50% of the groups' means being lower than 11.0 MPa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After bias risk analysis (Table 1), one study 11 was excluded due to its high risk of bias. Nine studies 2,3,8,[12][13][14][15][16][17] were included; descriptive data, random-effect means, confidence interval, and weight of each study are shown in Table 2. The lowest mean for bond strength in a group was 6.42 MPa; the highest value was 34.8 MPa, with 50% of the groups' means being lower than 11.0 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…1 Thus, two-step orthodontic adhesives, without prior application of adhesive resin, has appeared on the market in order to decrease the procedure time of bracket bonding. 2 These composites, called flowable resins, have a smaller amount of inorganic filler and therefore have low viscosity compared with conventional resins. 3 Furthermore, a previous report has shown that adhesive resins have greater cytotoxicity for gingival fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Cacciafesta et al (24) found bond strength to be significantly reduced by bleaching prior to bonding, whereas Hussein et al (25) found bond strength to be unaffected by the application of 12% chlorhexidine for 1 week prior to bonding, in an in vivo study. Additionally, Scribante et al (26) investigated the three different adhesives with two types of bracket base, finding Transbond XT to demonstrate the highest bond strength values. Aguiar et al (27) also evaluated the adhesives and their curing mode, reporting that the light activation of certain cement systems increases bond strength, although the curing mode does not affect bond strength in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…(13) La importancia de realizar este proceso es que permite simular el comportamiento clínico de los materiales dentales como las resinas. (16) En el presente estudio se efectuaron 500 ciclos de termociclado, similar a los estudios realizados por autores como Bishara y col (13) y Daub y col. (9) El (24) , Oliveira y col (25) encontraron valores promedio de resistencia al cizallamiento de 8.31 MPa y 10.61 MPa respectivamente para el cemento OrthoCem, similares a los encontrados en esta investigación. Esta discrepancia entre ambos cementos puede deberse a que el cemento OrthoCem presenta el primer y el cemento en la misma jeringa a diferencia del Transbond TM XT.…”
Section: Discussionunclassified